Searching for wheat resistance to aphids and wheat bulb fly in the historical Watkins and Gediflux wheat collections. (12th December 2016) - Aradottir, G.I.; Martin, J.L.; Clark, S.J.; Pickett, J.A.; Smart, L.E.
Abstract: Insect pests can reduce wheat yield by direct feeding and transmission of plant viruses. Here we report results from laboratory and field phenotyping studies on a wide range of wheat, including landraces from the Watkins collection deriving from before the green revolution, more modern cultivars from the Gediflux collection (north‐western Europe) and modern UK Elite varieties, for resistance to the bird cherry‐oat aphid, Rhopalosiphum padi (Homoptera: Aphididae) and the English grain aphid, Sitobion avenae (Homoptera: Aphididae). A total of 338 lines were screened for R. padi and 340 lines for S. avenae . Field trials were also conducted on 122 Watkins lines to identify wheat bulb fly, Delia coarctata, preference on these landraces. Considerable variation was shown in insect performance among and within different wheat collections, with reduced susceptibility in a number of varieties, but phenotyping did not identify strong resistance to aphids or wheat bulb fly. Field trials showed within collection differences in aphid performance, with fewer aphids populating lines from the Watkins collection. This differs from development data in laboratory bioassays and suggests that there is a pre‐alighting cue deterring aphid settlement and demonstrates differences in aphid preference and performance on older plants in the field compared with seedlings in the laboratory, highlighting the need for phenotyping for aphid resistance at different plant growth stages. No association was identified between performance of the different insect species on individual varieties, potentially suggesting different nutritional requirements or resistance mechanisms.